Penerapan Kekayaan Intelektual (KI) Terhadap Umkm Sebagai Upaya Mewujudkan Persaingan Bisnis Berkeadilan - Sulasno Sulasno (Universitas Serang Raya, 2018)
The existence of Micro, Small and Medium Enterprises (MSMEs) has a big contribution in advancing the economy of this nation. The growth and development of these MSMEs is able to drive the pace of the creative economy in the real sector and can be felt very beneficial in terms of the distribution of people's income. Especially if the product of the MSME product already has legal Intellectual property rights in its protection. Utilization of role of Intellectual Property by business actors towards UMKM products not yet maximal. The uneven understanding that Intellectual Property as the need for Protection makes many MSME products not yet registered. In addition, cost constraints and access difficulties are also considered as other causes. The research was made to answer the problem: 1) How is the Implementation of Intellectual Property Protection (KI) on the products of Micro, Small and Medium Enterprises (MSMEs)? 2) What is the role of the Government of Intellectual Property Protection (KI) on MSME products? The research method is carried out qualitatively with Descriptive-Normative analysis where Law acts as Norm / Rule / Legislation. Techniques Data collection by searching the literature and keeping in mind the prevailing reality. Result of the Research that in order to provide Legal Protection against UMKM products, the Government should play a role in facilitating the registration, relief and easy access to registration and socialization of Intellectual Property